Implementasi Manajemen Kurikulum Merdeka untuk Meningkatkan Inovasi Guru dalam Memenuhi Keragaman Peserta Didik di SMA Negeri 3 Yogyakarta - Hidayati, Wiji; Praptiwi, Niken; Arif Abdurravif; Arif Ihsannudin; Salma Aulia (Program Studi Manajemen Pendidikan Islam, 2024)
The independent curriculum has been implemented since the school year 2022/2023. Changes in the 2013 Curriculum to the Merdeka Curriculum demanded a quick adaptation from all parties. Factors such as school readiness and the role of teachers are crucial in the process of implementing. This study aims to determine the management and implementation of the Merdeka Curriculum policy in SMA Negeri 3 Yogyakarta. Writing this scientific article uses descriptive qualitative research methods. Data obtained through interviews, observation, and document review. The results showed that management played an active role in the preparation of curriculum implementation, as carried out by SMA Negeri 3 Yogyakarta. Although it is not a mobilization school and has only been running for one year, through the process of planning, development, implementation, and sustainable evaluation, SMA Negeri 3 Yogyakarta is able to implement the independent curriculum well.